X-y+z=5....(1)

2y+3z=14...(2)

-3y+2z=5...(3)

multiply by 3 in eq. (2) and multiply by 2 in eq. (3) add both equation

13z = 52

z = 4

put the value of z in eq. (2)

2y+3*4=14

2y+12=14

2y=2

y = 1

put the value of y and z in eq. (1)

x-1+4=5

x+3=5

x=2

so, the point is : (2,1,4)

2y+3z=14...(2)

-3y+2z=5...(3)

multiply by 3 in eq. (2) and multiply by 2 in eq. (3) add both equation

13z = 52

z = 4

put the value of z in eq. (2)

2y+3*4=14

2y+12=14

2y=2

y = 1

put the value of y and z in eq. (1)

x-1+4=5

x+3=5

x=2

so, the point is : (2,1,4)